1963
DOI: 10.1007/bf02518838
|View full text |Cite
|
Sign up to set email alerts
|

On the problem of trap‐response types of small mammal populations

Abstract: The mark-and-release method is basically useful in the study of population dynamics for small mammals, especially required in the research of long-term successive fluctuations in population parameters ; by this means we can obtain data for the estimation of N, B, P (in the terminology of LESLIE et al, 1952LESLIE et al, , 1953 and home range sizes at regular intervals during a study period, through which the population under study is expected to keep its natural status, suffering hardly so serious disturbance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

1966
1966
1982
1982

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 11 publications
2
14
0
1
Order By: Relevance
“…This is in agreement with other Apodemus studies (-) time of initial capture equal to mean time of recapture; (---) change in trapping programmes. (Gurnell, 1972;Tanaka, 1963). No general distinctions between trappability and sex ( Fig.…”
Section: Initial Capture and Recapture In Wood Micementioning
confidence: 99%
“…This is in agreement with other Apodemus studies (-) time of initial capture equal to mean time of recapture; (---) change in trapping programmes. (Gurnell, 1972;Tanaka, 1963). No general distinctions between trappability and sex ( Fig.…”
Section: Initial Capture and Recapture In Wood Micementioning
confidence: 99%
“…Clearly, it would be better to calculate such probabilities of capture from longer trapping periods. Gurnell (1976) reported that the probability of recapture in wood mice was greater than the probability of initial capture from a trapping study spanning three weeks, and this type of relationship has been demonstrated for several wild rodent species (Tanaka, 1963). Fig.…”
Section: Data Groupsmentioning
confidence: 91%
“…If the probability of initial capture equals the probability of recapture the regression lines in Fig. 1 should have a slope of 1.0 and pass through the origin; these would represent isoresponsive lines in the terminology of Tanaka (1963). Within each species the two variables are reasonably correlated: the correlation coefficient, r, for voles is 0.80; for mice without spring unmarked males 0.86; for mice with spring unmarked males 0.78.…”
Section: Frequency Of Capturementioning
confidence: 99%
See 1 more Smart Citation
“…Another advantage is that tracking is more independent of marking than is trapping, thereby conforming to the equal catchability assumption of mark-and-sample estimates. Tanaka (1963), Tanton (1965), and Marten (1970b) have reviewed the ways in which unequal catchabilities of marked and unmarked mice can inject a severe bias into markrecapture estimates.…”
Section: Advantages Of Trackingmentioning
confidence: 99%